USP46 Inhibits Cell Proliferation in Lung Cancer through PHLPP1/AKT Pathway - Wang, Wei (Biomed Res Int, 2020)
Previous studies have shown that ubiquitin-specific protease 46 (USP46) is a tumor suppressor in colon cancer and renal cell carcinoma. However, its specific role in other cancers is still poorly understood. This study is aimed at investigating the role of USP46 in lung cancer tumorigenesis and identifying its underlying mechanisms. Quantitative real-time polymerase chain reaction (qRT-PCR) and western blotting (WB) were used to measure the expression levels of USP46 and PHLPP1 in lung cancer tissue and adjacent normal tissue from patients with lung cancer. We examined the ability of USP46 to regulate cell proliferation in lung cancer cells via cell proliferation assay, radiation assay, genetic overexpression and knockdown, and chemical inhibition of relevant genes. We investigated the underlying mechanisms in multiple lung cancer cell line models by coimmunoprecipitation and ubiquitination assays. In this study, we identified a strong downregulation of the expressions of USP46 and PHLPP1 in lung cancer tissues relative to normal adjacent tissues. USP46 was further shown to inhibit lung cancer cell proliferation under conditions of normal growth and during radiation-induced DNA damage by antagonizing the ubiquitination of PHLPP1 resulting in the inhibition of AKT signaling. Exposure to radiation and AKT inhibition significantly reversed the effect of USP46 siRNA on lung cancer cell proliferation. USP46 is downregulated in lung cancer and suppresses the proliferation of lung cancer cells by inhibiting the PHLPP1/AKT pathway. AKT inhibition slows the proliferation of lung cancer cells that have been downregulated by USP46 and exposed to radiation. This suggests a potential therapeutic avenue for USP46-downregulated lung cancer through a combination of radiation and AKT inhibitor treatment.